Cerebrovascular Reactivity After Sport Concussion: From Acute Injury to 1 Year After Medical Clearance - Churchill, Nathan W.; Hutchison, Michael G.; Graham, Simon J.; Schweizer, Tom A. (Frontiers in Neurology, 2020)
Neuroimaging has identified significant disturbances in cerebrovascular reactivity (CVR) in the early symptomatic phase of concussion sport-related concussion. However, less is known about how whole-brain alterations in CVR evolve after concussion, and whether they remain present beyond medical clearance to return-to-play (RTP). In the present study, CVR was evaluated using blood-oxygenation level dependent functional magnetic resonance imaging (BOLD fMRI) during a respiratory challenge. Imaging data were collected for 110 university-level athletes, including 39 concussed athletes and 71 athletic controls. The concussed athletes were imaged at (1) the acute phase of injury (1 to 7 days post-injury); (2) the sub-acute phase (8 to 14 days post-injury); (3) medical clearance to RTP; (4) one month post-RTP; and (5) one year post-RTP. Enhanced negative BOLD response to controlled breathing was seen at acute injury, with attenuation of the effect mainly occurring by one year post-RTP. Secondary analyses showed that greater symptom severity and prolonged recovery were associated with enhanced BOLD response in the acute phase of injury, but a more attenuated BOLD response in the subacute phase. This study provides novel information characterizing the CVR response after a concussion and shows CVR to be a sensitive technique for evaluating long-term brain recovery.